Entrepreneurial attitudes in firms' credit access - Mehmet Civelek; Andrea Folvarčná; Ivan Brezina; Zuzana Veselá; Zdeněk Mikoláš (Contemporary Economics, 2023)
Although enterprises make significant contributions to the GDP of countries, bank credit access is one of the biggest obstacles for them to survive. However, businesses can signal their entrepreneurial behaviors that are included in the Theory of Planned Behavior (TPB) to reduce banks' concerns about their credit default. However, firms can have various entrepreneurial attitudes depending on their international activities that increase their innovativeness, and financial performance enabling credit access. Thus, the impact of TPB on credit access can differ depending on firms' internationalization status and this is the main of this study to examine. For this purpose, this paper analyzes 1175 firms from various countries. The researchers apply a purposive sampling method to create a research sample and direct an internet-mediated questionnaire to the selected respondents. Binary Logistic Regression analyses have been performed by the researchers to investigate the impact of TPB on credit access. The results show that the components of TPB, personal attitude, personal behavioral control, and subjective norms have different impacts on the credit access of international and domestic companies. Personal attitude and subjective norms negatively affect bank credit access of international and domestic firms, respectively while they do not determine credit access of domestic and international firms, respectively. Moreover, personal behav- ioral control positively affects credit access of domestic and international companies. The reason for these results might be related to firm-level and country-level characteristics. Relationship lending and the educational and financial support of academicians and policymakers can provide solutions for credit access problems of firms.
Keywords: G41; L25; M16; 330; theory of planned behavior; entrepreneurship; internationalization; bank finance; enterprises